EVALUACIÓN BACTERIOLÓGICA DE SEMEN DE VERRACOS USADOS COMO REPRODUCTORES EN GRANJAS PORCINAS DE LA ZONA DE LURÍN, LIMA - Conza B., Lidia (2004)
The objective of the present study was to evaluate the bacterial content in semen from 30 healthy boars used as sires in pig farms in the coastal area of southern Lima (Lurín). Half of boars were from two technically advanced farms and the other half from one semi technically oriented farm. The gloved-hand method for semen collection was used and the collected semen was filtered to separate the gel fraction. The results indicated that in the technical farms, 73% of ejaculates (11/15) showed bacterial growth and 13% (2/ 15) exceeded the OIE limit of 5,013 UFC/ml, whereas in the non-technical farm , all ejaculates showed bacterial growth and 60% (9/15) exceeded the OIE limit. Pseudomona aeruginosa was the bacteria with higher number of colonies per semen sample and Escherichia coli was the most common bacteria.